Genomic divergence across the tree of life - Rowan Hart; Nancy A. Moran; Howard Ochman (Proceedings of the National Academy of Sciences, 2025)
Nucleotide sequence data are being harnessed to identify species, even in cases in which organisms themselves are neither in hand nor witnessed. But how genome-wide sequence divergence maps to species status is far from clear. While gene sequence divergence is commonly used to delineate bacterial species, its correspondence to established species boundaries has yet to be explored across eukaryotic taxa. Because the processes underlying gene flow differ fundamentally between prokaryotes and eukaryotes, these domains are likely to differ in the relationship between reproductive isolation and genome-wide sequence divergence. In prokaryotes, homologous recombination, the basis of gene flow, depends directly on the degree of genomic sequence divergence, whereas in sexually reproducing eukaryotes, reproductive incompatibility can stem from changes in very few genes. Guided by measures of genome-wide sequence divergence in bacteria, we gauge how genomic criteria correspond to species boundaries in eukaryotes. In recognized species of eukaryotes, levels of gene sequence divergence within species are typically very small, averaging <1% across protein-coding regions in most animals, plants, and fungi. There are even instances in which divergence between sister species is the same or less than that among conspecifics. In contrast, bacterial species, defined as populations exchanging homologous genes, show levels of divergence both within and between species that are considerably higher. Although no single threshold delineates species, eukaryotic populations with >1% genome-wide sequence divergence are likely separate species, whereas prokaryotic populations with 1% divergence are still able to recombine and thus can be considered the same species.